2023
DOI: 10.32535/jicp.v6i1.2250
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Brand Trust on the Effect of Customer Experience and Engagement on Brand Loyalty: A Lesson From Bukalapak

Abstract: Intense competition among marketplaces in Indonesia caused Bukalapak traffic to decline significantly from 2019 to 2022 amid the growing number of @bukalapak Instagram followers. The authors believe that this decline is related to brand loyalty. Academic works stated that customer experience and engagement influence brand loyalty. However, brand trust mediation on that influence has not been thoroughly investigated. Therefore, this study aims to identify how brand trust mediates the effect of customer experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Research suggests that brand trust significantly influences consumers' online purchasing decisions. [23], [24] found that consumers are more likely to make purchases from brands they trust, even if alternative options are available. Factors such as brand reputation, product quality, and customer service contribute to building and sustaining trust in e-commerce contexts.…”
Section: Brand Trust and Online Purchasing Decisionsmentioning
confidence: 99%
“…Research suggests that brand trust significantly influences consumers' online purchasing decisions. [23], [24] found that consumers are more likely to make purchases from brands they trust, even if alternative options are available. Factors such as brand reputation, product quality, and customer service contribute to building and sustaining trust in e-commerce contexts.…”
Section: Brand Trust and Online Purchasing Decisionsmentioning
confidence: 99%